The Legal Consequences Of Legal Acts Continuation Based On Act Void Statement And Authorization By The Court - Brigitta Silitonga; Ok Saidin; Rosnidar Sembiring; Suprayitno, Suprayitno (SEAN Institute, 2024)
The deed of statement and deed of power of attorney made by a notary must be based on the principle of fairness. The principle of fairness emphasizes that every activity of the government or state administration must pay attention to the values that apply in society, whether related to religion, morals, customs, or other values. This is intended so that the making of the deed does not conflict with religion, morals, customs, or other values that apply in society. The next problem is regarding the rights of children to the joint property. This paper discussed the deed of Statement and Power of Attorney No. 33 dated July 27, 1998 made before Defendant II and its derivatives each dated July 27, 1998 canceled by the court, what is the civil liability of the Notary for the deed of statement and deed of power of attorney 0p-=that was canceled by the Court and what are the consequences of further legal actions based on the Deed of Statement and Power of Attorney that was canceled by the Court in the Supreme Court Decision Number 188 K/Pdt/2013 Jo. Number 443 PK/Pdt/2015. The method used is normative juridical legal research, namely: used to provide an overview that law is written regulations in the form of statutes. The reason why the Deed of Statement and Power of Attorney No. 33 dated July 27, 1998 made before Defendant II and its derivatives each dated July 27, 1998 was canceled by the court in connection with the evidence is because the Deed of Statement and Power of Attorney which has been proven with the theory of positive evidence exceeds the rights and interests of Defendant I, even the Plaintiff feels that Defendant II also has an interest, because the actions of Defendant II above are not in good faith.